(3QSGdI GdHdGZ hGdfgGjI aj GdJhMjO Edi cGaI GdehMOjf GdeJHQFjf ef GdJdMjOs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj,J (B433 (3g` s ((3MeRI Hf Ydi Hf CMeO s)
(3ChdgG (B:s
(3bO SeYJe eYGTQ GdehMOjf dehdGfG SHMGfg Ydjce ef fSN GdTQGFY hEfaQGO ehdGfG Ld PcQg hJfRjgg Yf GdHOGFY s
(3BNQgG (B:s
(3ajWGa Hg ai SGFQ GdHdOGf Edi Cf jHdZ Edi eOjfI jbGd dgG HdN JeJ QSGdI GdHdGZ hGdfgGjI HMeO ehdGfG hefg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B22s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3QSGdI ef QSGFd GdOQhRs
(3cJHJ HYV cdeGJgG HGdMeQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B79s
Keywords: (3GdJhMjO hGdedd hGdfMds